2017
DOI: 10.1016/j.trecan.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic DNA Damage Response: At the Crossroads of Structural and Numerical Cancer Chromosome Instabilities

Abstract: DNA double-strand breaks (DSBs) prevents cells from entering mitosis in the presence of genomic damage. Little is known about the response to DSBs once cells have already committed to mitosis. Here we review the genome-protective role of mitotic DNA damage response and evidence suggesting that its untimely activation induces chromosome segregation errors and paradoxically undermines genomic integrity. In contrast to normal cells, cancer cells coopt this pathway to propagate structural and numerical chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 64 publications
6
46
0
Order By: Relevance
“…Lagging chromosomes derived from unattached or mis-attached chromosomes, as well as from broken chromosomes lacking centromeric regions and kinetochore structures, produce structural alterations in cancer cells that result in whole chromosome gains and losses [25]. Lagging chromosomes can mis-segregate, leading to aneuploidy (i.e., numerical instability) and to translocations (i.e., structural instabilities) or can segregate as a form sequestered in micronuclei, which still results in effective aneuploidy [3]. A novel form of genetic instability known as "chromothripsis" is thought to be due, in part, to lagging chromosome pulverization [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lagging chromosomes derived from unattached or mis-attached chromosomes, as well as from broken chromosomes lacking centromeric regions and kinetochore structures, produce structural alterations in cancer cells that result in whole chromosome gains and losses [25]. Lagging chromosomes can mis-segregate, leading to aneuploidy (i.e., numerical instability) and to translocations (i.e., structural instabilities) or can segregate as a form sequestered in micronuclei, which still results in effective aneuploidy [3]. A novel form of genetic instability known as "chromothripsis" is thought to be due, in part, to lagging chromosome pulverization [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, DNA damage response (DDR) protects genome stability by acting during the interphase of the cell cycle. Recently, it has been demonstrated that DDR is also involved in chromosome segregation during mitosis progression in normal cells (i.e., mitotic DDR) [3]. In addition, a huge array of data point out that cancer cells may acquire the ability of distorting the protective role of mitotic DDR.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies on DNA damage responses have been done during interphase of the cell cycle. However, understanding the DNA damage response (DDR) during mitosis is also important since mutations accumulated during mitosis can lead to chromosomal aberrations, genomic instability of daughter cells, senescence and eventual cell death [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the signaling of ATR or ATM can keep the mitotic CDK1 kinase inactive through p53‐mediated expression of p21 WAF1/CIP1 or through CHEK1/CHEK2‐mediated activation of CDC25 proteins . Apart from such induced brakes to prevent mitotic entry, evidence has accumulated over the past years that several proteins involved in replication fork signaling and/or in DNA damage repair might also have central functions during the mitotic process in apparently undisturbed cells . It is largely unknown how their relative contributions to genome surveillance and to the regulation of mitotic progression are coupled.…”
Section: Introductionmentioning
confidence: 99%
“…3 Apart from such induced brakes to prevent mitotic entry, evidence has accumulated over the past years that several proteins involved in replication fork signaling and/or in DNA damage repair might also have central functions during the mitotic process in apparently undisturbed cells. [4][5][6][7][8][9] It is largely unknown how their relative contributions to genome surveillance and to the regulation of mitotic progression are coupled.…”
mentioning
confidence: 99%